Cessation of mass drug administration for lymphatic filariasis in Zanzibar in 2006: was transmission interrupted? - Maria P Rebollo; Khalfan A Mohammed; Brent Thomas; Shaali Ame; Said Mohammed Ali; Jorge Cano; Alba Gonzalez Escalada; Moses J Bockarie (Public Library of Science (PLoS), 2015)
BACKGROUND:Lymphatic filariasis (LF) is targeted for elimination through annual mass drug administration (MDA) for 4-6 years. In 2006, Zanzibar stopped MDA against LF after five rounds of MDA revealed no microfilaraemic individuals during surveys at selected sentinel sites. We asked the question if LF transmission was truly interrupted in 2006 when MDA was stopped. METHODOLOGY/PRINCIPAL FINDINGS:In line with ongoing efforts to shrink the LF map, we performed the WHO recommended transmission assessment surveys (TAS) in January 2012 to verify the absence of LF transmission on the main Zanzibar islands of Unguja and Pemba. Altogether, 3275 children were tested on both islands and 89 were found to be CFA positive; 70 in Pemba and 19 in Unguja. The distribution of schools with positive children was heterogeneous with pronounced spatial variation on both islands. Based on the calculated TAS cut-offs of 18 and 20 CFA positive children for Pemba and Unguja respectively, we demonstrated that transmission was still ongoing in Pemba where the cut-off was exceeded. CONCLUSIONS:Our findings indicated ongoing transmission of LF on Pemba in 2012. Moreover, we presented evidence from previous studies that LF transmission was also active on Unguja shortly after stopping MDA in 2006. Based on these observations the government of Zanzibar decided to resume MDA against LF on both islands in 2013.